Study on spatial distribution and connectivity of Tusi sites based on quantitative analysis - Huiwen Xiang; Mingjing Xie; Zongsheng Huang; Yu Bao (Ain Shams Engineering Journal, 2023)
The present study represents the spatial distribution and connection of Chinese Tusi architecture by using Thiessen polygons, fractal theory, and complex networks. The findings indicate that influenced by the concept of the Geomantic omen, the three Tusi sites share a significant degree of similarity in terms of location layout and architecture spatial distribution. Second, environmental factors play a dominant role in dividing network nodes into different clusters of aggregation, with minimal connectivity across clusters. Under the influence of social context, the network structure of the three sites exhibits multi-level centricity, with high-level building nodes, particularly administrative and religious structures, being extremely central. The spatial distribution and network connectedness of Tusi buildings show the merging of mountain nature and society, as well as the merger of ethnic minority cultures and the centralization system. Finally, this study suggests conservation and development strategies for the spatial morphology and network characteristics of Tusi sites.